Maternal exposure to deltamethrin during pregnancy and lactation impairs hippocampal learning and memory function of male offspring by ferroptosis - Shasha Huang; Wanqi Li; Dengke Wang; Huiwen Feng; Bo Wang; Xinyu Dong; Wei Zhao; Dan Liu; Yuan Wang (Ecotoxicology and Environmental Safety)
Deltamethrin (DM), a broad-spectrum insecticide, is widely used in the world. It can exert direct action on the central nervous system to produce neurotoxicity. Exposure to DM can lead to iron metabolism disorder, oxidative stress and learning and memory dysfunction. In our study, pregnant Wistar rats were randomly divided into four groups and gavaged at doses of 0, 1, 4 or 10 mg/kg/d DM from gestational day (GD) 0 to postnatal day (PND) 21. We used behavioral experiments and Nissl staining to observe the hippocampal development and learning and memory function of male offspring. In order to further confirm the regulation mechanisms of DM, we detected ferrous ion, oxidative stress, ferroptosis related proteins, phospholipase C (PL-C)/inositol triphosphate 3 receptor (IP3R) signaling pathway, intracellular Ca2+ and calcineurin (CaN) content in vivo. In vitro,we selected HT-22 cells to be exposed to DM under the intervention of ferrostatin-1 and pifithrin-α. Our results showed that maternal exposure to DM reduced T-maze correctness and the number of hippocampal neurons, and increased shuttle box passive avoidance rate. Moreover, maternal exposure to DM increased the expression of ferrous ion, malondialdehyde (MDA) and prostaglandin-endoperoxide synthase 2 (PTGS2) protein, and decreased the glutathione (GSH) level in the hippocampus, which was contributed to ferroptosis by p53-mediated solute carrier family 7 member 11 (SLC7A11)/glutathione peroxidase 4 (GPX4) axis in the male offspring. Furthermore, the ferroptosis caused by DM exposure could active PL-C/IP3R signaling pathway and increase the intracellular Ca2+ and CaN level, leading to an imbalance of calcium homeostasis in the hippocampus. Thus, maternal exposure to DM during pregnancy and lactation could impair hippocampal learning and memory function of male offspring by p53-mediated ferroptosis.